(untitled) (Journal of Student Affairs in Africa, 2021)
The Covid‑19 pandemic has had an unprecedented impact on faculty and student affairs practitioners which has changed the future of higher education worldwide. This reflective practitioner account looks into its impact on practitioners working in student affairs, some of which is not immediately visible, but unfortunately very significant and will surface in the medium and long term. There has been tremendous uncertainty for Student Affairs practitioners as a result of disruption from familiar routines and unexpected disengagement with their clients, the students. The change management perspective and scholarship of practice were adopted as methods of observing how a department in a university deals with unplanned change. The study concluded that the Covid‑19 pandemic impacted practitioners negatively at the case university as new skills were required, practitioners were required to adjust to new work arrangements, lost income, suffered mental health problems and faced resource constrains. Training and development, social media, employee support systems and employee incentives were catalysts in the early adoption of change.